Compressive Strength of Concrete Made from Aggregates of Different Sources (2018)
The use of substandard materials, particularly low quality concrete has been identified in literature as the leading cause of building collapse in Nigeria. The roadside artisans/bricklayers usually produce concrete for building construction without taking the aggregate source into consideration. This paper presents a comprehensive data on the compressive strength of concrete made from aggregates obtained from different sources in Ibadan, Nigeria. Experiments have been performed on 12 mixtures made up of fine aggregate from four sources and coarse aggregate from three different sources. The study utilize cement of the same strength (42.5R), coarse aggregate of the same size (10mm), the same water/cement ratio (0.6), and concrete mix (1:2:4) in order to determine the influence of aggregate source on concrete strength. Result revealed that only five mixtures had above the minimum cube compressive strength of 25N/mm2 recommended for the construction of the reinforced load-bearing building structural members. Three mixtures had above the cube compressive strength of 20N/mm2 recommended for use in plain concrete construction while the rest four mixtures had their cube strength between 19.3N/mm2 and 17.9N/mm2. Fine aggregate with higher compressive strength showed the lesser amount of deleterious materials. It was concluded that the compressive strength depend on aggregate source.